(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
Teaching classic literature comes with many challenges. Students today have a difficult time relating to century old texts that mostly reflect white male Euro-centric heteronormative values, yet English language arts teachers are required to teach classic literature at every grade level for high school students. This paper demonstrates how teachers can use culturally relevant teaching practices, including restory and critical literacy, to help students, particularly students of color and minorities, to engage with and create meaning from classic literature.